Experimental Study of Miscible Thickened Natural Gas Injection for Enhanced Oil Recovery - Al Hinai, N.; Saeedi, Ali; Wood, C.; Valdez, R.; Esteban, L. (American Chemical Society, 2017)
Hydrocarbon-miscible gas flooding typically involves injection of an associated gas (AG) mixture containing mainly methane (CH4) enriched with light hydrocarbon fractions and possibly acid gases. The AG mixture has been recognized as an excellent candidate for miscible gas injection (MGI). However, in general, the viscosity of the AG at reservoir conditions is significantly lower than that of crude oil leading to an unfavorable mobility ratio and low volumetric sweep efficiency during flooding. This study assesses the suitability of a library of commercially available polymers to thicken AG as a means of mobility control. The focus of the study is on the Field A located in the Harweel cluster in southern Oman. First, soluble polymeric thickeners for an AG mixture (CH4 60%, C2H6 9%, C3H8 6%, and CO2 25%) were identified using a parallel gravimetric extraction technique combined with cloud point measurements. Then, the viscosity of the identified soluble polymeric candidates in AG mixture was measured in a capillary viscometer at reservoir conditions. Three polymers were found to be completely or partially soluble in the AG mixture at 377 K and 55 MPa including poly(1-decene) (P-1-D), poly(methyl hydro siloxane) (PMHS), and poly(dimethylsiloxane) (PDMS). P-1-D found to be an effective thickener in AG mixture under conditions relevant to Field A, i.e., high temperatures and pressures. The polymer is soluble in the concentration range of 1.5–9 wt%. The viscosity of the P-1-D- thickened AG mixture increased by 2.2–7.4 times greater than AG mixture viscosity at 358–377 K. Furthermore, reservoir condition core flooding experiments were performed to examine the effectiveness of P-1-D-thickened AG gas mixture flooding to enhance oil recovery. The thickened-AG mixture flooding resulted in delayed gas breakthrough and subsequently 10–12% additional oil recovery.